Cooperation on Climate-Change Mitigation - Charles F. Mason; Stephen Polasky; Nori Tarui (Center for Economic Studies and ifo Institute (CESifo), 2016)
We model countries' choice of greenhouse gas (GHG) emissions as a dynamic game. Emissions generate immediate benefits to the emitting country but also increase atmospheric GHG concentrations that negatively affect present and future welfare of all countries. Because there are no international institutions capable of enforcing environmental agreements on sovereign nations, we analyze self-enforcing climate-change treaties that are supportable as subgame perfect equilibria. In simulations based on current conditions, we explore the structure of a selfenforcing agreement that achieves efficient climate change policy.
Keywords: Q54; C73; 330; international agreements; climate change; differential games